A Comparitive Study of On-Chip Clock Generators Using a-IGZO TFTs for Flexible Electronic Systems - Wadhwa, Nishtha (2018)
ECR/2017/000931. POCI-01-0145-FEDER-007688. No. 692373 (BET-EU). SFRH/BD/122286/2016.